The reaction of [Cp*IrCl2]2 with 2-methyl-1-butene-3-yne : formation of a η3-tetraenyl transition metal complex - Mak, Garvin Kar Hang (2014)
Reaction of the dimeric species [Cp*IrCl2]2 with 2-methyl-1-butene-3-yne results in C–C bond formation between two alkyne molecules and their coordination to an iridium center to form a complex containing a η3-tetraenyl ligand. The reaction pathway has been studied experimentally and computationally.